It's not a lie if you believe it: On norms, lying, and self-serving belief distortion - Cristina Bicchieri; Eugen Dimant; Silvia Sonderegger (The University of Nottingham, Centre for Decision Research and Experimental Economics (CeDEx), 2019)
This paper focuses on belief distortion in the context of lying decisions. We employ a twostage variant of the "dice under the cup" paradigm, in which subjects' beliefs are elicited in stage 1 before performing the dice task in stage 2. In stage 1, we elicit the subjects' beliefs about (i) majoritarian behavior or (ii) majoritarian normative beliefs in a previous session, and, in order to identify self-serving belief distortion, we vary whether participants are aware or unaware of the upcoming opportunity to lie in the dice task. We find that belief distortion occurs, but only with a specific kind of beliefs. When subjects are aware of the dice task ahead, they convince themselves that lying behavior is widespread in order to justify their lying. In contrast with beliefs about majority behavior, we find that beliefs about the extent to which lying is disapproved of are not distorted. Believing that the majority disapproves of lying does not inhibit own lying. These findings are consistent with a model where agents are conditional norm-followers, and where honest behavior is a strong indicator of disapproval of lying, but disapproval of lying is not a strong indicator of honest behavior.
Keywords: C72; C91; D8; D9; 330; Cheating; Experiment; Lying; Social Norms; Uncertainty